Taklif of Lunar and Solar Eclipse Prayers According to Fiqh and Scientific Perspective - Achmad Mulyadi Mulyadi (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2019)
The motion of earth, moon and sun result in natural phenomena which people can directly see and tangibly experience. They occur globally yet are experienced locally, such as the phenomenon of solar and lunar eclipses. In Islamic studies discussion, this leads to specific consequence relating to taklif (compulsion) of worship to perform eclipse prayers. Therefore, this study aims to elaborate whether the local eclipse phenomenon could apply the taklif globally. Another question is on when the obligation is urged to Moslem.Using the approach of fiqh and science through descriptive-analytic method, this study finds that in scientific perspective, both solar and lunar eclipses are sunnatullah or natural phenomenon relating to rotation of earth, moon and sun. From the earth, this phenomenon comes in two types of condition. First, it could be both computed and witnessed, while second, it could only computed but not everyone could eye-nakedly witness it. In fact, solar eclipse, for instance, although globally accessible through digital instruments, could be only manually seen in any local and limited area. Therefore, in the fiqh based perspective, the taklif of eclipse prayers only applies based on matlak wilayatul hukm. It is based on the strong belief that hisab indicates the occurrence of eclipse on any certain area in Indonesia and is empirically proved. The taklif, therefore, only applies for those who see the phenomenon, (Pergerakan bumi, bulan dan matahari mengakibatkan terjadi fenomena alam yang dapat dilihat dan dirasakan secara nyata. Fenomena ini bersifat glabal, akan tetapi dirasakannya secara local seperti fenomena gerhana matahari dan bulan. Dalam kajian keislaman, fenomena ini memunculkan akibat khusus yang berkaitan dengan taklif ibadah, yakni salat gerhana matahari dan bulan. Apakah fenomena gerhana yang bersifat lokal tersebut dapat berlaku secara global, dan kapan taklif tersebut terbebankan pada setiap umat muslim? Dengan pendekatan fiqh dan sains secara deskripstif analitis, artikel ini menemukan bahwa dalan perspektif sains, fenomena gerhana matahari dan bulan adalah sunnatullah yang berkaitan dengan rotasi bumi, bulan dan matahari. Bagi penduduk bumi, fenomena ini dapat dialami dalam dua kondisi, yaitu pertama, dikomputasi sekaligus disaksikan, dan kedua dikomputasi, akan tetapi tidak semua semua orang bisa menyaksikan. Karena itu, fenomena gerhana matahari walaupun dapat dikomputasi secara global, akan tetapi hanya dapat disanksikan secara lokal. Dengan demikian, dalam prsepektrif fiqh, taklif ibadah salat gerhana diberlakukan berdasarkan matlak wilayatul hukm, yaitu apabila diyakinkan bahwa secara hisab menunjukkan terjadi gerhana dalam kawasan tertentu di Indonesia dan dapat dibuktikan dengan fenomena empiriknya, maka taklif salat gerhana tersebut hanya berlaku bagi mereka yang menyaksikan fenomena gerhana tersebut.)